HUMAN RESOURCES CAPACITY OF NATIONAL VETERINARY SERVICES IN RUSSIAN FEDERATION TERRITORIAL SUBJECTS - M. A. Shibayev; I. M. Klinovitskaya; A. S. Oganesyan; A. V. Belchikhina; A. K. Karaulov (Ветеринария сегодня)
The paper presents the analysis results of basic quantitative characteristics of national veterinary service human resources as at 2017. The analysis was made both in general for the subject veterinary services and for their separate organizational levels: regional, local, laboratory as well as for the units, involved into the state veterinary surveillance on the regional level. The data about available number of veterinarians and stafng levels of veterinary institutions in the territorial subjects are discussed. These data suggest that the number of veterinarians correlates with the human and animal populations, as well as with the number of municipal entities and the volumes of livestock products manufactured. Notwithstanding the diverse peculiarities of the RF regions, the majority of them suﬀer from an actual defcit of veterinarians in the local and laboratory institutions. As of 2017, the average age of veterinarians in the RF is 40–45. The analysis of the RF average salaries showed that veterinarians of local and laboratory levels earn about 24 thousand rubles per month, which is 30% lower than the average level in Russia and almost twice lower than the salaries of regional veterinarians and ofcial veterinary inspectors. The study results are also indicative of a sufciently high number (about 72%) of veterinarians with a higher vocational education in RF Subject institutions, but at the same time not all of them are covered by advanced training programs.